Genetic architecture of barley (Hordeum vulgare L.) genotypes for grain yield and yield attributing traits - Swati, S; Tiwari, Kailash Chandra; Jaiswal, Jai Prakash; Kumar, Anil; Goel, Prashant (Journal of Cereal Research, 2018)
Combining ability for yield and its related traits was studied in 13 barley genotypes and their F1 progenies obtained through line x tester mating design. Significant differences for most of the traits in both gca and sca components revealed the importance of both additive and non-additive gene actions with the predominant effect of nonadditive gene action. Among parents, lines DWRB 134, BH 902 and RD2919 emerged as good general combiner for yield and importantcomponent traits whereas DWRUB 52 was identified as the best tester. Hence, these are considered as good general combiners for deriving desirable transgressive segregants for specific characters. However, line BH 902 emerged as good general combiner for maximum number of yield contributing traits i.e., peduncle length, spike length, awn length, productive tillers per plant, flag leaf area, number of grains per spike, weight of spike, 1000 grain weight, biological yield per plant and grain yield per plant. Among thirty crosses, seven displayed significant and positive specific combining ability (sca) effects for grain yield. Out of these seven crosses, four hybrids viz., BH 976 × RD 2849, DWRB 134 × DWRUB 52, BH 965 × DWRUB 52, BH 902 ×DWRB 101, were identified as the best promising combinations having good specific combining ability effects along with high per se performance for grain yield as well as other attributing characters in desired direction. The estimates of general combining ability (gca) effects as a whole suggested that if most of the characters are to be improved, inclusion of F1 hybrids showing high sca in crop improvement program and parents with good gca, into multiple crosses, bi-parental mating, and diallel selective mating could prove a worthwhile approach for tangible advancementof grain yield in barley. Doi.org/10.25174/2249-4065/2018/83148